2015
DOI: 10.1371/journal.pone.0127014
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness, a Marker of Subclinical Atherosclerosis, and Particulate Air Pollution Exposure: the Meta-Analytical Evidence

Abstract: IntroductionStudies on the association between atherosclerosis and long-term exposure to ambient air pollution suggest that carotid intima-media thickness (CIMT), a marker of subclinical atherosclerosis, is positively associated with particulate matter (PM) exposure. However, there is heterogeneity between the different studies concerning the magnitude of this association. We performed a meta-analysis to determine the strength of the association between CIMT and particulate air pollution.MethodsWe queried PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 44 publications
3
41
3
5
Order By: Relevance
“…31 Many studies have found associations between particulate air pollution and CIMT. 11,14,15 Particulate air pollution has been somewhat more consistently associated with CIMT than with CAC. This may be due in part to different ranges and composition of ambient particulate air pollution in various study regions.…”
Section: Discussionmentioning
confidence: 97%
“…31 Many studies have found associations between particulate air pollution and CIMT. 11,14,15 Particulate air pollution has been somewhat more consistently associated with CIMT than with CAC. This may be due in part to different ranges and composition of ambient particulate air pollution in various study regions.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, many studies have reported positive associations between particulate matter air pollution and CIMT. 14 15 27 Importantly, CIMT represents an earlier stage in vascular injury 64 than artery calcification, which only directly measures calcified elements. Perhaps relatively recent particulate matter pollution exposure contributes more to the development of soft plaque than to progression to arterial calcification, which may be more influenced by longer term exposures.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Possible mechanisms through which particulate matter could lead to atherosclerosis promotion include imbalance of the autonomic nervous system, a systemic oxidative stress and inflammatory response and, possibly, the transportation of particles directly into arterial blood circulation. 1 17-19 Even in regions with relatively low levels of fine particulate matter (aerodynamic diameter ≤2.5 µm, PM 2.5 ), studies have reported positive associations between PM 2.5 and cardiovascular or all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its first use [92], several cross-sectional studies have reported associations between home outdoor levels of air pollution and CIMT, including one which combined data from four cohort studies [93]. As summarised in a meta-analysis [94], both the cross-sectional and longitudinal associations between CIMT and air pollution were significant, although the associations between CIMT progression and long-term exposure were based on only three studies. However, another review [95] has not been able to demonstrate a clear association between CIMT progression and incident cardiovascular disease events, and so further work is needed to establish whether an increase in CIMT can be considered an indicator of adverse effects of air pollution on a chronic timescale.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%